Cardiovascular magnetic resonance assessment of left atrial size and function in endurance athletes - Javed, W.; Price, N. J.; Saunderson, C. E.; McDiarmid, A. K.; Erhayiem, B.; Farooq, M.; O'Neill, J.; Millar, L. M.; Malhotra, A.; Sharma, S.; Greenwood, J. P.; Plein, S.; et al. (Future Cardiology, 2022)
Background: Left atrial (LA) dilatation is linked to cardiovascular disease and atrial fibrillation but its associations in athletes are unknown. The authors investigated whether aerobic fitness and clinical parameters are associated with LA dilatation and emptying fraction (EF) in endurance athletes. Materials & methods: 65 endurance athletes underwent cardiovascular magnetic resonance to assess LA size and function along with fitness assessment. 25 sedentary controls underwent an identical cardiovascular magnetic resonance protocol. Results: In athletes, LA volume index was elevated, while total and passive LAEFs were decreased versus sedentary controls. Increasing age and maximal oxygen uptake were associated with LA volume index. Only older age was associated with decreased total LAEF. Conclusion: LA dilatation in athletes is associated with increasing age and aerobic fitness rather than conventional cardiovascular risk factors.